DIRDOP: a directivity approach to determining the seismic rupture velocity vector, Journal of Seismology - Caldeira, B. (2009)
Directivity eff ects are a characteristic of seismic source finiteness and are a conse- quence of the rupture spread in preferential di- rections. These eff ects are manifested through seismic spectral deviations as a function of the observation location. The directivity by Doppler effect method permits estimation of the direc- tions and rupture velocities, beginning from the duration of common pulses, which are identified in waveforms or relative source time functions. The general model of directivity that supports the method presented here is a Doppler analy- sis based on a kinematic source model of rup- ture (Haskell, Bull Seismol Soc Am 54:1811–1841, 1964) and a structural medium with spherical sym- metry. To evaluate its performance, we subjected the method to a series of tests with synthetic data obtained from ten typical seismic ruptures. The experimental conditions studied correspond with scenarios of simple and complex, unilater- ally and bilaterally extended ruptures with dif- ferent mechanisms and datasets with diff erent levels of azimuthal coverage. The obtained re- sults generally agree with the expected values. We also present four real case studies, applying the method to the following earthquakes: Arequipa, Peru (Mw = 8.4, June 23, 2001); Denali, AK, USA (Mw = 7.8; November 3, 2002); Zemmouri– Boumerdes, Algeria (Mw = 6.8, May 21, 2003); and Sumatra, Indonesia (Mw = 9.3, December 26, 2004). The results obtained from the dataset of the four earthquakes agreed, in general, with the values presented by other authors using different methods and data.